Shopping Experience of Indonesian Diaspora in Europe Related to Primark's Reputation and Customer Attitude towards Unethical and Unsustainable Business Practice Brands - Yulia Tricahyaningtyas; Ratu Livani; Susilowati Natakoesoemah (AIBPM Publisher, 2023)
When Primark is alleged to be an unethical and unsustainable fashion brand after the accident in Bangladesh in 2013, we would like to know further about the public’s response as well as their attitude toward fast fashion brands selling cheap clothes, including Primark. With such a reputation, we also want to get a deeper yet broader range of understanding by conducting interview with our respondents who are Indonesian diaspora (who have been to Europe) and some European citizens. We asked them about their point of view and their experience in purchasing items both in fast fashion and sustainable fashion brands. The research method used is qualitative, with interviews as a data collection technique. The result showed that the reputation of Primark as a fast fashion brand as well as its accusation of unethical and unsustainable business practices, affect consumer behavior in purchasing fashion products. Brand reputation also has a strong connection between consumer attitude and buying decisions. Despite buying decisions with sustainable brands not yet done hugely by now, consumers have started to rethink shopping with fashion brands that practice business against the law and norms regarding society and the environment.